Impact Assessment of Floating and Alternative Feeds (Wolffia globosa) for Fish Rearing Technologies in Tripura, India - Sharma, Lajit Kumar; Lahiri, Biswajit; Singh, Yumlembam Jackie; Waikhom, Gusheinzed; Biswas, Pradyut; Hoilenting; S. T., Pavan Kumar; Chandegara, Abhay Kumar; Meinam, Martina (Indian Journal of Extension Education, 2025)
The study assessed the social, economic, and environmental impacts of floating feed– and Wolffia-based fish rearing technologies disseminated by the College of Fisheries, CAU (Imphal), Lembucherra, Tripura. An after-only design was employed with 140 respondents: 100 floating feed adopters chosen through simple random sampling and 40 Wolffia adopters through complete enumeration. Impact indicators across social, economic, and environmental domains were developed using SMART criteria, expert-validated, and analysed with the Wilcoxon Signed-Rank Test, paired t-tests, and Spearman’s correlation. Floating feed adoption improved production (+16.75 kg cycle⁻¹), net returns (+Rs. 6,644.26), and feed efficiency [Apparent feed conversion ratio (AFCR) –0.23], raising the Economic Impact Score from 32.93 to 40.23 (p = 0.000). Social participation, awareness, and income increased, while the Environmental Impact Score fell from 23.996 to 19.146, reflecting improved water quality. Wolffia adoption also enhanced production (+18.48 kg cycle⁻¹), returns (+Rs. 4,804.35), and AFCR (–0.25), contributing to livelihoods, nutrition, and climate-resilient aquaculture. Major constraints included high floating feed price, supplier dependence, flood-induced losses, and weak extension support. Overall, both technologies boosted aquaculture productivity, profitability, and sustainability, highlighting the need for technical services, training, and institutional support.